Vpliv polimorfizma glutationskih S transferaz na pojav sekundarnih novotvorb po zdravljenju levkmije v otroštvu - Jazbec, Janez (Zdravniški vestnik, 2004)
Background. Survivors of childhood leukemia have an increased risk of developing second malignant neoplasms and specific treatment factors such as alkylating agents, topoisomerase inhibitors and radiation have been associatedwith their occurrence. Genetic polymorphism in drug-metabolizing enzymes may result in impared detoxification of chemotherapeutics and may leadto increased risk for cancer. Methods. To test if polymorphism in glutathione S-transferases (GST) genes is associated with occurrence of secondary malignant neoplasms, we compared GSTM1, GSTT1 and GSTP1 genotypes among 16 patients treated for childhood leukemia in whom second neoplasm occurred and matched the control group. Results. GSTM1 null genotype was foundin 44% of patients with second neoplasms and in 50% in control group (p =0.768), GSTT1 null genotype in 19% of cases and in 29% of controls (p = 0.729) and GSTP1105Ile/ile in 50% of cases and 37% of controls (p = 0.537). Differences in distribution of GST genotypes in patients with second neoplasrrts after childhood leukemia, compared to a matched control group of patients were not statistically significant. Conclusions. In our study we werenot able to show relation between GST genotype and occurrence of second neoplasms after the childhood acute leukemia.
Keywords: Analysis; Child; Classification; Genotip; Genotype; Glutathione Transferases; Leukemia; Levkemija; Neoplasms, Second Primary; Novotvorbe, druge primarne; Otrok; Physiopathology; Polimorfizem (genetika); Polymorphism (Genetics); Therapy